SERVICE QUALITY, PERCEIVE VALUE, SATISFACTION, TRUST, DAN LOYALTY PADA PT. KERETA API INDONESIA MENURUT PENILAIAN PELANGGAN SURABAYA - Hatane Semuel; Nadya Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2009)
This research is to analyze service performance of PT Kereta Api Indonesia (KAI) from five dimensions of SERVQUAL. It is also to analyze the relationship among service quality, perceived value, customer satisfaction, trust and customer loyalty. The populations of this research are all train passengers who have used the service of PT KAI in Surabaya station.The writer uses convenience sampling by distributing questionnaires to 400 respondents from some departing train stations in Surabaya. The results show that service performance of PT KAI, according to its customers, is good. In addition to this, the research also shows that SRVQUAL and perceived value has direct positive influences on customer satisfaction, and customer satisfaction has a direct positive influence on trust and customer loyalty. In the analysis, it also shows that trust has a positive influence on customer loyalty, eventhough it is not significant. Thus, customer satisfaction has become an intervening variable between SERVQUAL and perceived value towards customer loyalty. It also serves as an intervening variable between SERVQUAL and perceived value towards trust. However, trust cannot serve as an intervening variable between customer satisfaction and customer loyalty.